An investigation on the lubrication mechanism of MoS2 nanoparticles in unidirectional and reciprocating sliding point contact: The flow pattern effect around contact area. (June 2018) - Wu, Hongxing; Li, Xing; He, Xingliang; Lu, Jie; Wang, Liping; Zhou, Bin; Dong, Guangneng
Abstract: The goal of the work is to investigate the flow pattern of MoS2 nanoparticles, which influences the lubrication properties of the lubricant. The tribological behavior of MoS2 nanoparticles was studied in unidirectional or reciprocating ball-on-disk sliding tribometer. Friction reduction of 0.25 wt% MoS2 nanoparticles in reciprocating mode reached 53.1% compared with that of base oil; whereas the friction coefficient of 0.25 wt% MoS2 nanoparticles in unidirectional mode was similar with that of base lubricant (about 0.18). Flow pattern results of MoS2 nanoparticles around contact area show that particles piled up heavily in the inlet of contact zone in unidirectional mode, leading to starved lubrication. However, loose net-like aggregations were formed in reciprocating mode, benefiting to reduce friction and wear. Highlights: Lubrication behavior of MoS2 nanoparticles additives is dependent on sliding contact conditions. Reciprocating sliding induces formation of lubrication beneficial net-like clusters with MoS2 nanoparticles. Lubricant starvation caused by the piled up nano-MoS2 in unidirectional sliding impairs the lubrication performance. Tribological behavior is dominated by the flow pattern of nano-MoS2 .